LEGAL CONSCIOUSNESS AS A SUBJECT OF INTERDISCIPLINARY RESEARCH - Шелих, Андрій (Київський національний університет імені Тараса Шевченка, 2025)
Background. The complexity and multifaceted nature of legal consciousness necessitates interdisciplinary research of this phenomenon in various fields of scientific knowledge. Thus, legal consciousness is the subject of scientific research in legal theory and philosophy, psychology, sociology and other sciences. Analysis of modern interdisciplinary approaches will allow the formation of the main essential characteristics of legal consciousness and identify effective ways to increase its level, which, in turn, is a necessary prerequisite for the formation and development of civil society in Ukraine. Methods. In conducting scientific research, general scientific methods such as analysis, synthesis, deduction, and analogy were used. Given the essence of legal consciousness as a legal phenomenon, private scientific methods of legal cognition, namely comparative legal and logical-legal methods, were also applied. Results. The peculiarities of understanding the phenomenon of legal consciousness in such branches of scientific knowledge as law, philosophy, psychology and sociology are studied. The main structural elements of legal consciousness are characterized as a means of reflecting legal reality and effectively influencing it. Within the framework of the philosophical paradigm, the value of legal consciousness for forming a legal state and civil society is revealed. The phenomenon of legal consciousness is studied as a subject of psychological and sociological science, as a result of which the mechanisms of influence on the formation of the necessary level of legal consciousness of citizens are clarified. Conclusions. Legal consciousness is an extremely complex category, a system of interacting and mutually coordinated elements aimed at the subjective perception of legal reality and its active influence on it. Among the structural elements of legal consciousness, it is possible to distinguish legal knowledge, ideas, feelings, emotions and ideas about law. The complex interaction of these elements in the human mind allows individuals to form a positive attitude towards law and, as a result, to implement the rule of law. However, despite the legal component of legal consciousness, to form a holistic idea of legal consciousness, it is not enough to study it exclusively within the framework of the doctrine of law. In turn, it is possible to reveal the content of this category only by applying an interdisciplinary approach. Therefore, the analysis of existing achievements in philosophy, psychological science and sociology will provide an expanded understanding of the value of legal consciousness and mechanisms of psychological influence on individuals to increase legal consciousness.

Вступ. Комплексність і багатоаспектність явища правосвідомості зумовлює необхідність міждисциплінарних досліджень цього явища в різних галузях наукового знання. Правосвідомість є предметом наукового пошуку не лише у сфері теорії права, а й у філософії, психології, соціології та інших науках. Аналіз сучасних міждисциплінарних підходів дозволить сформувати основні сутнісні характеристики правової свідомості й виявити ефективні шляхи підвищення її рівня, що, у свою чергу, є необхідною передумовою становлення та розвитку громадянського суспільства в Україні.  Методи. У процесі наукового дослідження були застосовані такі загальнонаукові методи, як аналіз, синтез, дедукція та аналогія. З огляду на сутність правосвідомості як правового явища були застосовані також приватнонаукові методи юридичного пізнання, а саме порівняльно-правовий і логіко-юридичний. Результати. Досліджено особливості розуміння явища правосвідомості в таких галузях наукового знання, як право, філософія, психологія та соціологія. Надано характеристику основних структурних елементів правосвідомості як засобу відображення правової дійсності й ефективного впливу на неї. У межах філософської парадигми розкрито цінність правосвідомості для формування правової держави та громадянського суспільства. Досліджено явище правосвідомості як предмет психологічної та соціологічної науки, у результаті чого з'ясовано механізми впливу на формування необхідного рівня правосвідомості громадян. Висновки. Правосвідомість – це надзвичайно складна категорія, що є системою взаємодіючих і взаємоузгоджених елементів, націлених на суб'єктивне сприйняття правової дійсності й активного впливу на неї. Серед структурних елементів правосвідомості можна виокремити правові знання, ідеї, правові почуття, емоції та уявлення стосовно права. Комплексна взаємодія вказаних елементів у свідомості людини дозволяє сформувати в індивідів позитивне ставлення до права і, як наслідок, упровадження верховенства права. Однак, незважаючи на правовий складник правової свідомості, для формування цілісного уявлення про правосвідомість недостатньо досліджувати її виключно в межах доктрини права. У свою чергу, розкрити зміст цієї категорії можна лише шляхом застосування міждисциплінарного підходу. Отже, аналіз існуючих здобутків у сфері філософії, психологічної науки та соціології забезпечить розширення уявлень про цінність правосвідомості й механізми психологічного впливу на індивідів із метою підвищення рівня правосвідомості.
ПРАВОСВІДОМІСТЬ ЯК ПРЕДМЕТ МІЖДИСЦИПЛІНАРНИХ ДОСЛІДЖЕНЬ
Keywords: law; legal consciousness; legal reality; society; civil society; legal state; philosophy; legal psychology; sociology; rule of law; legal regulation; право; правосвідомість; правова дійсність; суспільство; громадянське суспільство; правова держава; філософія; правова психологія; соціологія; верховенство права; правове регулювання